1982
DOI: 10.1073/pnas.79.21.6656
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the immunoglobulin J chain from the mouse.

Abstract: The primary structure of the murine J chain was investigated by sequence analysis ofthe J chain cDNA inserts from two independently cloned chimeric plasmids. The sequence data showed that (i) the two cDNA inserts accounted for all but approximately 100 5' nucleotides of the J chain mRNA and (ii) the J chain mRNA encodes a prepeptide of at least 23 amino acids, a mature protein of 137 residues, and an untranslated 3' region of 707 nucleotides exclusive of the 3' poly(A) tract. The amino acid sequence deduced fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
2

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 31 publications
(26 reference statements)
1
26
2
Order By: Relevance
“…Our model of the J chain as a single immunoglobulin-like domain contrasts with the two-domain model previously proposed by Cann et al (12). The two-domain structure was deduced from the differences observed in the properties of the amino-terminal and carboxyl-terminal halves of the J polypeptide.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Our model of the J chain as a single immunoglobulin-like domain contrasts with the two-domain model previously proposed by Cann et al (12). The two-domain structure was deduced from the differences observed in the properties of the amino-terminal and carboxyl-terminal halves of the J polypeptide.…”
Section: Discussioncontrasting
confidence: 41%
“…Recently, the complete primary structures of human and mouse J chains have become available from analyses of amino acid and nucleotide sequences (11)(12)(13). In the studies reported here, advantage was taken of these data to deduce the secondary structure of the J chain and to test the prediction by comparing the circular dichroism (CD) properties of the isolated J chain before and after renaturation.…”
mentioning
confidence: 99%
“…Substitution of either of the Cys residues of the J chain involved in disulfide bond formation with the ␣-chain yielded IgA monomers with covalent J chain (20). The disulfide structure is not consistent with previous models of the J chain structure (21,22) but suggests that the J chain is positioned between two IgA dimers linked tail-to-tail. C ␣ 3 with the associated tail piece but not C ␣ 2 is required for J chain incorporation into IgA (23).…”
Section: Discussioncontrasting
confidence: 37%
“…Twenty micrograms of RNA was used for each sample analyzed. J chain mRNA was identified with a 1.2-kb cDNA fragment from plasmid Jc21 (45). PU.1 mRNA was identified with a 0.4-kb SacI cDNA fragment derived from pBSKS-PU.1 (46).…”
Section: Northern Blotsmentioning
confidence: 99%
“…However, some appeared not to express Ig, despite the fact that they retained the functionally assembled Ig genes (␥2b and/or ) of the plasmacytoma parent. For this reason, we analyzed a large number of these hybrids (45) to obtain a reliable estimate of this protein's rescuing function. Thirty-five continued to express Ig, as determined by ELISA, whereas ten did not (data summarized in Table I).…”
Section: The C-terminal Domain Of Oct-2 Is Required For Its Unique Fumentioning
confidence: 99%